Візуальні форми та їх роль у модерністському романі (“Чотири шаблі” Юрія Яновського) - Мовчан, Р. (Слово і Час, 2018)
Розгляд “Чотирьох шабель” Ю. Яновського крізь призму поетики візуальності відкриває
нові смислові грані цього репрезентативного для 1920-х років твору. Його візуальний простір
розширює історичний час до меж екзистенційного сприйняття. У статті аналізуються візуальні
описи, образи, засоби, прийоми (“картини, що оживають”, кіномонтаж, візуальні деталі, ілюстрація
В. Кричевського до видання 1930 р. та ін.), їхня функціональна роль у структурі українського
модерністського роману. Compared to realism, the modernism of the 1920s had a broader use of visual forms. Its immanent
features and syncretism of the Ukrainian art of the period are the main reasons for that. Visual forms of
art were especially prominent at this time (painting, cinema, theater, architecture). The first avant-garde
tendencies appeared in these art forms and later permeated literature, changing its genres and style.
While describing the modern time we can mention the ‘all-seeing eye’ (M. Bakhtin) of numerous writers
of the period, their ability to see the world through visual images, impressions, details. New verbal and
visual genre and style forms appear (or reappear and become active if they existed before): visual
poetry, prose, screen novel, movie essay etc. Visual elements of other art forms permeate the literary
texts. At this time greater polyphony of encoded meanings and their various readings become possible.
The “Four Sabres” novel by Yuriy Yanovskyi is typical for the 1920s. Its visual forms are an important
part of the author’s modernist individual style. They originate in cinema. One may talk of cinema
(visual) nature of this author’s world perception.
The analysis of the work in the light of visual poetics shows new semantic facets and deepens its
modern interpretation. The novel’s visual space expands the historical time to the limits of existential
perception. The paper analyzes visual descriptions, images, means, methods (‘living pictures’, montage,
visual details), their functional role in the structure of Ukrainian modernist novel. The verbal photo
shot in Yanovskyi’s work is compared to the illustration by Vasyl Krychevskyi (the 1930 edition), which
complements it and deepens the idea of the author’s historiosophy.